2005
DOI: 10.1007/s11060-005-6747-7
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of High Grade Gliomas and Diffuse Intrinsic Pontine Tumors of Childhood and Adolescence: A Historical – and Futuristic – Perspective

Abstract: Pediatric high grade gliomas represent a heterogeneous group of tumors with poor prognoses despite the use of multimodal treatment. Very little progress has been made over the past decades in identifying efficacious therapeutic modalities against both high grade gliomas and diffuse brainstem gliomas in children. The degree of surgical resection is the most important clinical prognostic factor for children with high grade gliomas, and a complete resection should be attempted whenever feasible. The role of radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 109 publications
1
68
0
2
Order By: Relevance
“…In this small series of eight patients exposed to BBBD and carboplatin or methotrexate, a median time to progression of 15 months, and a median survival of 27 months were deemed promising. In this type of tumor, survival beyond 2 years is exceptional, and it really is the first time that a chemotherapy trial is reported to impact outcome (64).…”
Section: Clinical Results Obtained With the Bbbd Procedure In The Trmentioning
confidence: 99%
“…In this small series of eight patients exposed to BBBD and carboplatin or methotrexate, a median time to progression of 15 months, and a median survival of 27 months were deemed promising. In this type of tumor, survival beyond 2 years is exceptional, and it really is the first time that a chemotherapy trial is reported to impact outcome (64).…”
Section: Clinical Results Obtained With the Bbbd Procedure In The Trmentioning
confidence: 99%
“…Further analysis of the CCG-945 study showed that a significant number of patients were misclassified by institutional review and revised by a consensus neuropathology review as low-grade tumors. 88,89 This is critical when assessing outcome of other treatment trials, and it highlights the importance of a central review process in pediatric gliomas. Since then, multiple trials investigated different chemotherapy regimens for the treatment of pediatric high-grade gliomas.…”
Section: Chemotherapymentioning
confidence: 99%
“…While initial trials by the CCG demonstrated improvements in PFS in patients treated with a combination of chemotherapy and radiation after resection, later trials were unable to replicate the initial findings [2,11,15]. Lack of new chemo-therapeutic combinations in the immediate postresection stage has kept the 5-year overall survival from high grade astrocytomas between 10-20% [1,3,16].…”
Section: Discussionmentioning
confidence: 99%
“…Initial trials by the Children's Cancer Group (CCG) in children with HGG treated with post-radiation chemotherapy (vincristine, lomustine and predinose) had an improved progression free survival (PFS) of 46% compared to 26% of those treated with radiation alone [15].Despite these initial findings, successive chemotherapeutic trials were unable to significantly improve outcomes [3,11]. Promising data has been published in adult patients with HGG treated with the methylating agent Temozolamide when administered with concurrent radiation therapy, suggesting a role for adjuvant chemotherapy in pediatric patients as well although subsequent trials have been slow to demonstrate similar improvement [1].…”
Section: Introductionmentioning
confidence: 99%